Impaired olfactory neural circuit in patients with SLE at early stages. (June 2021) - Chen, Chen; Kong, Wei; Liang, Jun; Lu, Jiaming; Chen, Dajie; Sun, Yi; Zhang, Xin; Qing, Zhao; Feng, Xuebing; Sun, Lingyun; Zhang, Bing
Objective: To investigate the changes of olfactory function and odor-induced brain activation in patients with systemic lupus erythematosus (SLE) at early stages compared with healthy controls. Materials and Methods: Olfactory function and odor-induced brain activation in 12 SLE patients at early stages and 12 age, gender and education matched healthy controls were evaluated using olfactory behavior test and odor-induced task-functional magnetic resonance imaging (task-fMRI). Results: No significant differences in olfactory behavior scores (including olfactory threshold, olfactory identification, and olfactory memory) were found in the patients with SLE at early stages compared with the healthy controls, while significantly decreased odor-induced activations in olfactory-related brain regions were observed in the patients. In the SLE group, the patients with better performance in the olfactory threshold test had significantly lower levels of anti-dsDNA antibody. Conclusion: The current study demonstrated that significant alterations in odor-induced brain activations occurred prior to measurable olfactory decline in SLE at early stages, which provided a new method for early diagnosis of olfactory dysfunction in SLE.